Unraveling the development of cutaneous neurofibromas in neurofibromatosis type 1 - Pernelle Pulh; Fanny Coulpier; Audrey Onfroy; Layna Oubrou; Wanzhen Zhang; Léa Toledano; Elie Abou Zougheib; Laura Fertitta; Pierre Wolkenstein; Piotr Topilko (Acta Neuropathologica Communications)
Abstract Neurofibromatosis type 1 (NF1) is a genetic disorder that leads to the formation of cutaneous neurofibromas (cNFs), benign nerve sheath tumors that develop in the skin and significantly impact the quality of life of patients. cNF development begins with bi-allelic NF1 loss in the Schwann cell (SC) lineage, followed by the recruitment of a complex tumor microenvironment consisting of fibroblasts, immune cells, blood vessels, axons, and a dense extracellular matrix. Despite its high prevalence and clinical impact, the molecular mechanisms underlying cNF formation remain poorly understood. Here, we used an Nf1 knockout (Nf1-KO) mouse model combined with immunohistochemistry and single cell transcriptomics in order to investigate the mechanisms driving cNF development. Our results showed that mutant SCs accumulate in the skin of young mice weeks prior to the onset of cNF. However, these cells remain quiescent until triggered by skin trauma, which induces their proliferation and the rapid formation of cNFs. Using a trauma-induced Nf1-KO model with scRNAseq, we designed a transcriptomic atlas of growing and mature cNFs, as well as adjacent apparently healthy skin. This analysis identified a population of non-myelinating Aquaporin1highNestinlow SCs as the likely cells of origin for cNFs. These cells overexpress genes involved in axon growth and guidance, potentially driving the abnormal innervation observed in both mouse and patient cNFs. In addition, we found that tumor SCs, along with dermal and/or epineurial fibroblasts and pericytes, overexpress genes encoding collagen, contributing to the extensive fibrosis characteristic of cNFs. Notably, all of these cells exhibit high expression of periostin and tenascin C, key extracellular matrix components, highlighting them as novel therapeutic targets in view of cNF treatment.